Nieznana oprawa dla Jana Łaskiego w Bibliotece Uniwersyteckiej w Poznaniu. Przyczynek do badań nad italianizmem w introligatorstwie polskim XVI wieku - Wagner, Arkadiusz (Biblioteka Uniwersytecka w Poznaniu, 2012)
Punktem wyjścia artykułu jest analiza nowo odkrytej oprawy z księgozbioru Jana Łaskiego (1499–1560). Nacisk położono na charakterystyczne składniki italianizującej dekoracji okładzin. Dzieło zostało osadzone na tle renesansowego introligatorstwa włoskiego, w tym głównie dorobku introligatorów skupionych w środowisku weneckim. Osobną uwagę poświęcono superekslibrisowi w formie naśladującej charakterystyczny typ włoskiej tarczy herbowej testa di cavallo. W dalszej części poruszono kwestię miejsca wykonania oprawy oraz jej autora. Z dokonanej analizy porównawczej z italianizującymi oprawami krakowskimi z lat 20. XVI wieku wynika, że jest to dzieło Macieja z Przasnysza, określanego w literaturze jako Mistrz Główek Anielskich. Zaawansowane formy renesansowe dzieł tego introligatora, w tym oprawy z poznańskich zbiorów, przesądzić muszą o uznaniu go za czołowego europejskiego twórcę, błyskawicznie przyswajającego nawet najświeższe tendencje w introligatorstwie Italii.

The present article begins with an analysis of a binding from the book collection of Jan Łaski (1499–1560) that has been recently discovered. The description aims to focus on characteristic elements indicating the Italian influence in the ornamentation of the covers. The characteristic features of the work are compared against the background of Italian Renaissance bookbinding traditions, in particular with that of the bookbinding workmanship distinguishing and representative of the group of bookbinders from Venice. A particular attention is given to the superexlibris stamped on the front cover with its form copying the characteristic type of the Italian shield of testa di cavallo form. The author then proceeds to discuss the issue of the place of manufacture of the binding and its authorship. The provided comparative analysis with other Italian-influenced bindings manufactured in Cracow in the 1520s shows that its authorship can be attributed to Maciej of Przasnysz, defined in literature as the Master of Cherub Heads. Advanced Renaissance forms in the works of this bookbinder, including the bindings from the Poznań collection, may prove him to be one of the leading European book artisans, who was capable of immediate absorbing the most recent and contemporary trends in bookbinding in Italy.
On the unknown binding of a book from Jan Łaski book collection currently held at Poznań University Library. A contribution to the study on the Italian influences in Polish bookbinding of the sixteenth century
Keywords: Łaski Jan; Joannes a Lasco; Maciej z Przasnysza; introligatorstwo renesansowe; Renaissance bookbinding; italianizm; Italianism (Italian influences); Italianism (Italian influences); oprawa książkowa; superekslibris; superexlibris; bookbinding; master of Cherub Heads